THE USE OF DIGITAL STORYTELLING TOWARDS STUDENTS’ COMPETENCY IN WRITING TEXT - Tarigan, Karisma Erikson; Liana, Liana (STMIK Widya Cipta Dharma, 2018)
The main objective of this research is to prove whether the digital storytelling enhances and improve students writing competency. The study uses classroom action research (CAR). The data in this study are quantitative and qualitative data. The quantitative data will be collected by using the essay test. The qualitative data will be collected by using observation, field notes, and questionnaire. The score of students’ writing descriptive text kept increasing from pre-test until post-test. It was proved by the data which showed that the mean of the students’ score in post-test II is 86.6 (92.75%) was higher than the post-test I is 72.2 (68.75%), and also higher than the pre-test 54.8 (25%). The response of student in using digital storytelling in the agree category, it can be seen from the 15 students who passed the KKM (70) and 1 student still low of KKM. The class percentages of post-test II show improvements from the previous test; the improvement is 67.75%. The frequencies of item agree appear 110 times or (52.88%). Furthermore, it can be concluded that Digital Storytelling is effective and useful to be used in teaching writing skill, especially in Descriptive Text.